2008
DOI: 10.3844/ajassp.2008.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fasteners Disposition on Behaviour of Timber-Framed Walls with Double Fibre-Plaster Coating Boards

Abstract: This paper provides experimental analysis of timber-framed walls, coated with double fibreplaster coating boards fastened to the timber frame. As the walls under a horizontal load actually behave like a deep composite beam, the fasteners disposition is very important and directly influences bearing capacity and stiffness of the wall. Therefore, three different groups of test samples with staple distances of s = 37.5, 75 and 150 mm were experimentally analysed and compared. For groups G2 and G3 the failure of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Numerical results showed that the wall elements with OSB (Oriented strand board) sheathing board have higher racking resistance than walls with fibre-plaster boards irrespective of the spacing between fasteners, and they are recommended for use in tall timber-framed buildings located in very windy or earthquakeprone areas. An experimental analysis on the influence of fastener spacing for fibre-plaster board has been presented in [23] for single fibre-plaster sheathing boards, and in [24] for double fibre-plaster boards. Results for different fastener spacings of 37.5 mm, 75 mm and 150 mm showed that the bending stiffness of a timber-framed wall strongly depends on the fastener spacing s and is higher the smaller the distance between staples.…”
Section: Analytical Calculation Of Stiffness Of Timber-framed Wallmentioning
confidence: 99%
“…Numerical results showed that the wall elements with OSB (Oriented strand board) sheathing board have higher racking resistance than walls with fibre-plaster boards irrespective of the spacing between fasteners, and they are recommended for use in tall timber-framed buildings located in very windy or earthquakeprone areas. An experimental analysis on the influence of fastener spacing for fibre-plaster board has been presented in [23] for single fibre-plaster sheathing boards, and in [24] for double fibre-plaster boards. Results for different fastener spacings of 37.5 mm, 75 mm and 150 mm showed that the bending stiffness of a timber-framed wall strongly depends on the fastener spacing s and is higher the smaller the distance between staples.…”
Section: Analytical Calculation Of Stiffness Of Timber-framed Wallmentioning
confidence: 99%
“…Since the wall element is treated as a composite system, the wall's behaviour strongly depends on the fasteners disposition, which is already experimentally tested on wall elements with doubled FPB on each side [11]. Therefore, it is interesting to analyse a fully new possible technological solution when the FPB are not mechanically connected to the timber frame, but they are glued to the timber studs and girders.…”
Section: Fem Analysis -Fpb Are Glued To the Timber Framementioning
confidence: 99%